(untitled) (Journal of the Bangladesh Agricultural University, 2018)
This study reports on the suitable formulation of cake using potato and peanut flour with wheat flour. Fresh potato and peanut were analyzed for their chemical compositions and then dried in cabinet dryer. Four samples of cake: containing wheat flour only; containing 70% wheat flour, 5% potato flour and 25% peanut flour; containing 70% wheat flour, 15% potato flour and 15% peanut flour; and containing 70% wheat flour, 20% potato flour and 10% peanut flour were analyzed for proximate compositions. The properties of cakes were evaluated in terms of volume, moisture content, weight, and crumb and crust characteristics. The prepared cake samples were also judged in categories of color, flavor, texture and overall acceptability. Among the formulations, cake sample containing 70% wheat flour, 15% potato flour and 15% peanut flour secured the highest score with respect to color, texture and overall acceptability. Finally, the storage stability of the composite cake, packaged with single layer polythene, was evaluated in terms of moisture uptake by storing it in room temperature (25°C). J. Bangladesh Agril. Univ. 16(2): 315-321, August 2018